2021
DOI: 10.1002/jcop.22591
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal ideation among active and nonactive/former Latter‐day Saint sexual minorities

Abstract: Sexual minorities (SMs) in the Church of Jesus Christ of Latter-day Saints (LDS) experience a number of unique risks related to their religious/spiritual and SM experience that may increase their likelihood of experiencing suicidal ideation (SI) and ultimately dying by suicide. However, it is unclear which aspects of these experiences are responsible for elevated SI. It is further unclear whether religiousness/ spirituality and minority stress relate to SI similarly for active and nonactive/former LDS SMs. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 52 publications
(93 reference statements)
4
32
0
Order By: Relevance
“…For example, participants reported higher divine and doubt-related struggles than most samples. Most alarmingly, similar to prior research on sexual minorities (Lefevor, McGraw, & Skidmore, 2022) and TGNC+ individuals (Exline et al, 2021), this sample reported strikingly high interpersonal struggles. This finding makes sense given how much religion-based interpersonal stigma sexual minorities often encounter (Lefevor et al, 2021; Lefevor, Etengoff, et al, 2022) and given that interpersonal R/S struggles are “conflicts with other people and institutions about sacred issues; anger at organized religion; and feeling hurt, mistreated, or offended by others in relation to religious or spiritual issues” (Pargament & Exline, 2022, p. 9).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…For example, participants reported higher divine and doubt-related struggles than most samples. Most alarmingly, similar to prior research on sexual minorities (Lefevor, McGraw, & Skidmore, 2022) and TGNC+ individuals (Exline et al, 2021), this sample reported strikingly high interpersonal struggles. This finding makes sense given how much religion-based interpersonal stigma sexual minorities often encounter (Lefevor et al, 2021; Lefevor, Etengoff, et al, 2022) and given that interpersonal R/S struggles are “conflicts with other people and institutions about sacred issues; anger at organized religion; and feeling hurt, mistreated, or offended by others in relation to religious or spiritual issues” (Pargament & Exline, 2022, p. 9).…”
Section: Discussionsupporting
confidence: 78%
“…However, higher R/S struggles were predicted by a current Christian R/S affiliation and by childhood or current involvement in an R/S community perceived as less LGBQ+ affirming. These findings are consistent with minority stress theory (Meyer, 2003), multilevel stigma theory (White Hughto et al, 2015), and social stigma process theory (Frost, 2011) in that exposure to a stigmatizing religious context is often a significant source of external minority stress for R/S sexual minorities (Anderton et al, 2011; Lefevor, Etengoff, et al, 2022; Lefevor, McGraw, & Skidmore, 2022).…”
Section: Discussionsupporting
confidence: 76%
“…To resolve sexual identity confusion and/or conflict they must navigate their communities’ expectations of gender conformity and marriage. These individuals may garner support from conservative religious communities that may simultaneously buffer and perpetuate psychological distress (Lefevor, McGraw, & Skidmore, 2021). Therapists should be mindful that for many LGB clients raised in conservative religious environments, making a shift to a more progressive faith tradition may not be easy or possible and that clients may interpret encouragement to do so as evidence that the therapist does not understand them.…”
Section: Important Considerationsmentioning
confidence: 99%
“…Older cohorts of sexual minorities are more likely to remain religious, and religion and spirituality may figure more prominently in therapy with them. For some, religious engagement may provide needed social support (Lefevor, McGraw, & Skidmore, 2021) while for others, it may ignite sexual identity confusion and/or conflict.…”
Section: Age-related Considerationsmentioning
confidence: 99%
“…Coming out to others is linked to an increase in minority stressors such as discrimination and internalized stigma (e.g., Russell and Fish 2016), particularly when coming out to individuals in religions that do not affirm same-gender sexuality or gender expression outside of assigned birth sex (Rosati et al 2020 ). It is therefore unsurprising that SGMs are much more likely to conceal their sexual orientation or gender identity if they are religious or spiritual (Kubicek et al 2009; Lefevor, McGraw et al, 2022 ; Shilo and Savaya 2012; Woodyard et al 2000).…”
Section: Difficulties and Benefits Of Coming Out To Religious Othersmentioning
confidence: 99%